FACTORII CE INFLUENȚIAZĂ REALIZAREA CONSTITUȚIEI ȘI CONSOLIDAREA REGIMULUI CONSTITUȚIONALITĂȚII ÎN STATUL DE DREPT - Costachi, Gheorghe (SUPREMANCE OF LAW, 2017)
Currently, the legal and political supremacy of the Constitution and its social value within a state are practically undisputed. Constitution has become a standard and a fundamental pillar of social, political and legal life of the society, aroused a great scientific interest for analyzing and explaining it as a multilateral phenomenon. In this study we propose a concise approach to the problem of achievement of the Constitution to strengthen the constitutionality regime in the rule of law and identifying the positive and negative factors what influences this process.
Keywords: Constitution; action of the Constitution; achievement of the Constitution; influencing factors; the constitutionality regime; the rule of law